Experimental insight into the proximate causes of male persistence variation among two strains of the androdioecious Caenorhabditis elegans (Nematoda) - Schulenburg Hinrich; Wegewitz Viktoria; Streit Adrian (BMC Ecology, 2008)
Abstract Background In the androdioecious nematode Caenorhabditis elegans virtually all progeny produced by hermaphrodite self-fertilization is hermaphrodite while 50% of the progeny that results from cross-fertilization by a male is male. In the standard laboratory wild type strain N2 males disappear rapidly from populations. This is not the case in some other wild type isolates of C. elegans, among them the Hawaiian strain CB4856. Results We determined the kinetics of the loss of males over time for multiple population sizes and wild isolates and found significant differences. We performed systematic inter- and intra-strain crosses with N2 and CB4856 and show that the males and the hermaphrodites contribute to the difference in male maintenance between these two strains. In particular, CB4856 males obtained a higher number of successful copulations than N2 males and sired correspondingly more cross-progeny. On the other hand, N2 hermaphrodites produced a higher number of self-progeny, both when singly mated and when not mated. Conclusion These two differences have the potential to explain the observed variation in male persistence, since they should lead to a predominance of self-progeny (and thus hermaphrodites) in N2 and, at the same time, a high proportion of cross-progeny (and thus the presence of males as well as hermaphrodites) in CB4856.